ANALYSIS OF PTKIN SCIENCE LABORATORY NEEDS IN WEST SUMATRA - Zulpadrianto, Zulpadrianto (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2023)
Science laboratory needs analysis research has been conducted. This study aims to analyze the laboratory needs of PTKIN in West Sumatra. This analysis includes organizational structure, management personnel needs and laboratory development. The results showed that the organizational structure of the science laboratory at PTKIN West Sumatra had been arranged. However, PTKIN in West Sumatra still lacks laboratory management personnel so that a formula is developed to calculate personnel needs. Furthermore, the laboratory needs to evaluate the governance and development of laboratory functions. The function that was previously only as a place of education needs to be improved as a place of research. The development of research laboratories is in line with increasing the volume of research equipment, K3 laboratories and professional personnel in their fields.